Integral Integral16

Calculus Level 3

0 1 log ( k = 0 5 x k ) d x = 1 2 ( a + π b + log ( c ) ) \large \int_0^1 \log \left(\sum _{k=0}^{5} x^k\right) \, dx=\frac{1}{2} \left(-a+\pi \sqrt{b}+\log (c)\right)

where a , b , c a,b,c are positive integers. Submit a + b + c a+b+c .

Note: Also see this problem .


The answer is 445.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Dec 22, 2017

I = 0 1 log ( k = 0 5 x k ) d x = 0 1 log ( 1 x 6 1 x ) d x = 0 1 log ( 1 x 6 ) d x 0 1 log ( 1 x ) d x By integration by parts = x log ( 1 x 6 ) 0 1 + 0 1 6 x 6 1 x 6 d x 0 1 log x d x Using a b f ( x ) d x = a b f ( a + b x ) d x = x log ( 1 x 6 ) 0 1 6 0 1 ( x 6 x 6 1 ) d x x log x x 0 1 = x log ( 1 x 6 ) 0 1 6 0 1 ( 1 x 6 1 + 1 ) d x ( 1 ) \begin{aligned} I & = \int_0^1 \log \left(\sum_{k=0}^5 x^k \right) dx \\ & = \int_0^1 \log \left(\frac {1-x^6}{1-x} \right) dx \\ & ={\color{#3D99F6}\int_0^1 \log \left(1-x^6\right) dx} -\color{#D61F06} \int_0^1 \log \left(1-x\right) dx & \small \color{#3D99F6} \text{By integration by parts} \\ & = {\color{#3D99F6}x\log (1-x^6)\bigg|_0^1 + \int_0^1 \frac {6x^6}{1-x^6} dx} -\color{#D61F06} \int_0^1 \log x\ dx & \small \color{#D61F06} \text{Using }\int_a^b f(x) \ dx = \int_a^b f(a+b-x) \ dx \\ & = {\color{#3D99F6}x\log (1-x^6)\bigg|_0^1 - 6 \int_0^1 \left(\frac {x^6}{x^6-1}\right) dx} -\color{#D61F06} x \log x - x \bigg|_0^1 \\ & = x\log (1-x^6)\bigg|_0^1 - 6 \int_0^1 \left({\color{#3D99F6}\frac 1{x^6-1}}+1\right) dx -\color{#D61F06} (- 1)\end{aligned}

= x log ( 1 x 6 ) 6 0 1 1 ( x 1 ) ( x + 1 ) ( x 2 x + 1 ) ( x 2 + x + 1 ) d x 6 0 1 d x + 1 = x log ( 1 x 6 ) 0 1 6 0 1 1 6 ( 1 x 1 1 x + 1 + x 2 x 2 x + 1 x + 2 x 2 + x + 1 ) d x 5 = x log ( 1 x 6 ) 0 1 log ( x 1 ) 0 1 + log ( x + 1 ) 0 1 1 2 0 1 2 x 1 3 x 2 x + 1 d x + 1 2 0 1 2 x + 1 + 3 x 2 + x + 1 d x 5 = x log ( 1 x 6 ) 0 1 log ( 1 x ) 0 1 + log 2 + 1 2 log ( x 2 + x + 1 x 2 x + 1 ) 0 1 + 2 0 1 1 2 3 ( x 1 2 ) + 1 d x + 2 0 1 1 2 3 ( x 1 2 ) + 1 d x 5 = x log ( 1 x 6 1 x ) 0 1 + log 2 + log 3 2 + 3 tan 1 ( 2 x 1 3 ) 0 1 + 3 tan 1 ( 2 x + 1 3 ) 0 1 5 = x log ( k = 0 5 x k ) 0 1 + log 2 + log 3 2 + π 3 6 + π 3 3 5 = log 6 + log 2 + log 3 2 + π 3 2 5 = 1 2 ( 10 + π 3 + log 432 ) \begin{aligned} \ \ & = x\log (1-x^6) - 6 \int_0^1 {\color{#3D99F6}\frac 1{(x-1)(x+1)(x^2-x+1)(x^2+x+1)}} dx - 6 \int_0^1 dx + 1 \\ & = x\log (1-x^6)\bigg|_0^1 - 6 \int_0^1 {\color{#3D99F6}\frac 16 \left( \frac 1{x-1} - \frac 1{x+1} + \frac {x-2}{x^2-x+1} - \frac {x+2}{x^2+x+1} \right)} dx - 5 \\ & = x\log (1-x^6)\bigg|_0^1 - \log(|x-1|)\bigg|_0^1 + \log(x+1)\bigg|_0^1 - \frac 12 \int_0^1 \frac {2x-1-3}{x^2-x+1}dx + \frac 12 \int_0^1 \frac {2x+1+3}{x^2+x+1} dx - 5 \\ & = x\log (1-x^6)\bigg|_0^1 - \log(1-x)\bigg|_0^1 + \log 2 + \frac 12 \log \left(\frac {x^2+x+1}{x^2-x+1}\right)\bigg|_0^1 + 2 \int_0^1 \frac 1{\frac 2{\sqrt 3}\left(x-\frac 12\right)+1}dx + 2 \int_0^1 \frac 1{\frac 2{\sqrt 3}\left(x-\frac 12\right)+1}dx - 5 \\ & = x\log \left(\frac {1-x^6}{1-x} \right) \bigg|_0^1 + \log 2 + \frac {\log 3}2 + \sqrt 3 \tan^{-1} \left(\frac {2x-1}{\sqrt 3}\right) \bigg|_0^1 + \sqrt 3 \tan^{-1} \left(\frac {2x+1}{\sqrt 3}\right) \bigg|_0^1 - 5 \\ & = x\log \left(\sum_{k=0}^5 x^k \right) \bigg|_0^1 + \log 2 + \frac {\log 3}2 + \frac {\pi\sqrt 3}6 + \frac {\pi\sqrt 3}3 - 5 \\ & = \log 6 + \log 2 + \frac {\log 3}2 + \frac {\pi \sqrt 3}2 - 5 \\ & = \frac 12 (-10 + \pi \sqrt 3 + \log 432 ) \end{aligned}

a + b + c = 10 + 3 + 432 = 445 \implies a+b+c = 10+3+432 = \boxed{445}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...